In case you get hit by a bus : how to organize your life now for when you're not around later - Schneiderman, Abby; Seifer, Adam; Newman, Gene (Workman Publishing, 2020)
"A step-by-step program for getting your life in order, so you're prepared for the unexpected. The odds of getting hit by a bus are 495,000 to 1. But the odds that you're going to die some day? Exactly. Even the most disorganized among us can take control of our on- and off-line details so our loved ones won't have to scramble later. The experts at Everplans, a leading company in digital life planning, make it possible in this essential and easy-to-follow book. Breaking the task down into three levels, from the most urgent (like granting access to passwords), to the technical (creating a manual for the systems in your home), to the nostalgic (assembling a living memory), this clear, step-by-step program not only removes the anxiety and stress from getting your life in order, it's actually liberating. And deeply satisfying, knowing that you're leaving the best parting gift imaginable. When you finish this book, you will have: A system for managing all your passwords and secret codes Organized your money and assets, bills and debts A complete understanding of all the medical directives and legal documents you need--including Wills, Powers of Attorney, and Trusts A plan for meaningful photos, recipes, and family heirlooms Records of your personal history, interests, beliefs, and life lessons An instruction manual for your home and vehicles Your funeral planned and obituary written (if you're up for it)"--